Trade Union Power, Threat Effects and the Extent of Organization - Rosen, S. (Review of Economic Studies, 1969)
Journal Article Trade Union Power, Threat Effects and the Extent of Organization Get access S. Rosen S. Rosen University of Rochester and National Bureau of Economic Research Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 2, April 1969, Pages 185–196, https://doi.org/10.2307/2296836 Published: 01 April 1969 Article history Received: 10 June 1968 Revision received: 14 November 1968 Published: 01 April 1969